Uticaj amplifikacije na doživljaj slušnog hendikepa kod osoba sa prezbiakuzijom - Ostojić Zeljković, Sanja; Nikolić, Mina; Matić, Ivana; Kovačević, Tamara; Đoković, Sanja (Specijalna edukacija i rehabilitacija, 2024)
Introduction. Presbycusis can have numerous consequences, particularly hearing impairment and impairment in oral communication, which can severely affect the psychological, emotional and social lives of older people. Numerous factors related to age-related hearing loss (time of onset, degree of hearing loss), as well as the wide range of socioeconomic factors, may contribute to the subjective perception of hearing impairment in individuals with presbycusis. In line with previous research on this topic, the question arises whether there is a difference between hearing aid users and non-users in the perception of hearing loss. Objective. To find out whether there is a difference in the subjective perception of hearing loss between people with presbycusis who use hearing aids and those who do not. Method. The sample consisted of 56 people diagnosed with presbycusis. Questionnaires for general demographic data, the Hearing Handicap Inventory for the Elderly Screening Version (HHIE-S) and the International Outcome Inventory – Hearing Aids (IOI-HA) were used. Results. All individuals without amplification in this study had higher scores on the HHIE-S and confirmed hearing impairment, while 62.1% of those with amplification considered themselves disabled due to presbycusis. Hearing aid users generally had high scores on the IOI-HA, which leads us to conclude that hearing aids are extremely useful for the daily living and functioning of individuals with presbycusis. Conclusion. The results of the study emphasize the importance of using hearing aids in people with presbycusis, regardless of the degree of hearing loss and the age of the user.
Keywords: presbycusis; hearing loss; amplification; quality of life